Cinta Tanah Air pada Era Digital: Peran Generasi Z dalam Mempertahankan Identitas Nasional - Muhammad Arya Pradipta; Abdul Wafi; Marita Marita; Rahmadani Luthfiah; Fariz Ikhsan; Prawidya Raihan Syafaat (Populer: Jurnal Penelitian Mahasiswa, 2024)
Generation Z (born between 1997 and 2012) has been socialised in the digital age, which has informed their social interactions and cultural awareness. This study assesses the role of Generation Z in maintaining national identity in the context of globalisation, employing a Likert-scale interview methodology with university students aged 18–22 at Universitas Gadjah Mada. The results indicate that the majority of respondents exhibit a robust sense of patriotism (53.6% strongly agree) and express support for the preservation of national identity (70% agree/strongly agree). However, a small percentage of respondents express doubt (18.4%) or disagreement (5.2%). Generation Z proactively employs social media to advance local culture, address social issues, and reconcile global influences with local values. Despite the challenges posed by globalisation, they demonstrate a commitment to maintaining Indonesia's cultural heritage. This study recommends culturally relevant education tailored to the digital era to support Generation Z in preserving national identity while adapting to global developments.